Effectiveness of a multifaceted intervention to improve emergency department care of low back pain: a stepped-wedge, cluster-randomised trial. Issue 10 (10th March 2021) - Coombs, Danielle M; Machado, Gustavo C; Richards, Bethan; Needs, Chris; Buchbinder, Rachelle; Harris, Ian A; Howard, Kirsten; McCaffery, Kirsten; Billot, Laurent; Edwards, James; Rogan, Eileen; Facer, Rochelle; et al.
Abstract : Background: Overuse of lumbar imaging is common in the emergency department (ED). Few trials have examined interventions to address this. We evaluated the effectiveness of a multifaceted intervention to implement guideline recommendations for low back pain in the emergency department. Methods: We conducted a stepped-wedge, cluster-randomised trial in four EDs in New South Wales, Australia. After a 13-month control phase of usual care, the EDs received a multifaceted intervention to support guideline-endorsed care in a random order, based on a computer-generated random sequence, every 4 weeks over a 4-month period. All sites were followed up for at least 3 months. The primary outcome was the proportion of low back pain presentations receiving lumbar imaging. Secondary healthcare utilisation outcomes included prescriptions of opioid and non-opioid pain medicines, inpatient admissions, length of ED stay, specialist referrals and re-presentations. Clinician beliefs and knowledge about low back pain care were measured before and after the intervention. Patient-reported pain, disability, quality of life and satisfaction were measured at 1, 2 and 4 weeks post ED presentation. Results: A total of 269 ED clinicians and 4625 episodes of care for low back pain (4491 patients) were included. The data did not provide clear evidence that the intervention reduced lumbar imaging (OR 0.77; 95% CI 0.47 to 1.26; p=0.29). It did reduce opioid use (OR 0.57; 95% CI 0.38 to 0.85; p=0.006) and improved clinicians' beliefs (mean difference (MD), 2.85; 95% CI 1.85 to 3.85; p<0.001; on a scale from 9 to 45) and knowledge about low back pain care (MD, 0.48; 95% CI 0.13 to 0.83; p<0.01; on a scale from 0 to 11). There was no difference in pain scores at 1-week follow-up (MD, 0.04; 95% CI −1.00 to 1.08; p=0.94; on a scale from 0 to 10). A similar trend was observed for all other patient-reported outcomes and time points. This study found no effect on the other secondary healthcare utilisation outcomes. Conclusion: It is uncertain if a multifaceted intervention to implement guideline recommendations for low back pain care decreased lumbar imaging in the ED; however, it did reduce opioid prescriptions without adversely affecting patient outcomes. Trial registration number ACTRN12617001160325.